Migraine: an overview to the therapeutic approach in the emergency room - Mesa Navas, Miguel Antonio; Vagner Ramírez, Basilio (Medicina UPB, 2010)
Acute management of migraine is a challenging process in the emergency medical service. Its treatment should be based on symptom severity in order to define a stratified approach. In cases with moderate to severe symptoms the agents of choice are the triptans, specific antimigraine agents that provide swift relief of pain and improvement in the overall discapacity. Such treatment should be initiated in the early stages of pain and before the instauration of the cutaneous allodinia phenomenon in order to secure an optimal response to such treatment.
Keywords: migraine disorder; therapeutics; emergency medical service